New synthetic route to ethynyl-dUTP: A means to avoid formation of acetyl and chloro vinyl base-modified triphosphates that could poison SELEX experiments. Issue 4 (15th February 2017) - Röthlisberger, Pascal; Levi-Acobas, Fabienne; Hollenstein, Marcel
Graphical abstract: Mild acidic treatment of a precursor in the synthesis of the widely used 5-ethynyl-2′-dUTP leads to the formation of chlorovinyl- and acetyl-modified nucleosides. The corresponding triphosphates were shown to be good substrates for numerous DNA polymerases and thus represent a hazard for SELEX experiments since they can block sites from further modification by CuAAC. In order to circumvent the formation of these side-products, a new synthetic route is presented. Abstract: 5-Ethynyl-2′-deoxyuridine is a common base-modified nucleoside analogue that has served in various applications including selection experiments for potent aptamers and in biosensing. The synthesis of the corresponding triphosphates involves a mild acidic deprotection step. Herein, we show that this deprotection leads to the formation of other nucleoside analogs which are easily converted to triphosphates. The modified nucleoside triphosphates are excellent substrates for numerous DNA polymerases under both primer extension and PCR conditions and could thus poison selection experiments by blocking sites that need to be further modified. The formation of these nucleoside analogs can be circumvented by application of a new synthetic route that is described herein.